(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article explores the establishment of Science Olympiads in secondary schools, examining the impact of reforms on STEM education. Through a comprehensive literature analysis, it evaluates the methods used in implementing Science Olympiads, analyzes the results, and discusses their implications. The article concludes with suggestions for further improvements in STEM education through Science Olympiads.